Effect of Work Life Balance and Organizational Commitment on Turnover Intention of Employees of PT. Santosa Adi Perkasa - Hasan Sahroni; Uce Karna Suganda (Kontigensi : Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the effect of work life balance and organizational commitment on employee turnover intention of PT. Santosa Adi Perkasa. The data used in this study are primary and secondary data obtained from companies and literature. The sampling technique in this study used the census method and the data collection techniques used in this study were interviews, questionnaires, observations, and questionnaires. Respondents in this study were company employees totaling 100 people. This research uses Multiple Correlation Analysis method. The results of this study indicate that work life balance has a significant effect on turnover intention, and organizational commitment has a significant effect on turnover intention, the results also show that work life balance and organizational commitment have a significant effect on turnover intention.